Fast Forward to the Past: Revisiting Trauma after the Fall - Sánchez-Palencia, Carolina; Almagro, Manuel (Miscelánea: A Journal of English and American Studies, 2012)
The representation of traumatic experience usually brings to the surface an element that has been long repressed. To a great extent it also implies “breaking the silence” imposed by an authoritarian voice proposing a one-dimensional version of the historical Real. This paper analyses the way in which some recent films —which dramatize the collateral effects of the collapse of Communist regimes— offer new representations of actual historical events and address a common and, at the same time varied, European concern for coming to terms with a recent traumatic past. The films feature their protagonists trapped in a characteristic traumatic paradox as they have to reconcile testimonial accuracy with the essential ineffability of their experiences. However, guided by a common desire to rewrite the past and to heal personal and collective wounds, they resort to the materiality of objects which function as what Pierre Nora terms ‘lieux de mémoire’, that is, new signifiers for the (re)creation of a different History.
Keywords: Trauma; Historiography; Fall; Revision; Memory; Re-writing